English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

rectangular form...

a. y = (3/4)x - 1/2

b. y = (4/3)x + 2/3

c. y = (4/3)x - 5/3

d. y = (3/4)x + 5/4

e. y = (1/3)x + 2/3

f. y = (1/3)x + 10/3

g. y = 4x - 5

h. y = (1/4)x + 5/4

or none of these

2007-06-08 09:15:32 · 2 answers · asked by Doug 2 in Science & Mathematics Mathematics

2 answers

Since x = 2 + 4t, and y = 3 + t

t = y-3

x = 2 + 4(y-3)
x = 2 + 4y - 12
x = 4y - 10
x + 10 = 4y
(1/4)x + 5/2 = y

None of those.

2007-06-08 09:19:50 · answer #1 · answered by Nicknamr 3 · 1 0

x= 2 + 4t --> t = (x-2)/4
y= 3 + t --> t= y-3
Thus y-3 = (x-2)/4
4y-12 =x-2
4y = x +10
y = (1/4)x +5/2

Answer is none of these.

2007-06-08 10:33:21 · answer #2 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers